HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP MOTIVASI IBU DALAM PEMERIKSAAN IVA TEST - Herniyatun, Herniyatun; Dewi, Siti Utami; Mauludiyah, Zaida; Sulistyowati, Endang; Yulita, Hendra (Ensiklopedia of Journal, 2024)
Cervical cancer is the second most common cancer in women worldwide. It is estimated that every year there are around 32,469 new cases of Indonesian women detected with cervical cancer and 23,300 women die. The number of childbearing age couples who perform VIA tests is very small compared to the number of PUS in the Bangkinang Health Center Working Area, Kampar district. Precisely in Laboy Jaya Village, the number of PUS is 503 couples. The purpose of the study was to determine the relationship between knowledge and attitudes towards maternal motivation in the VIA test. Type of quantitative research with cross sectional design. The research was conducted in 2022 with a sample of 125 people. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed there was a relationship between knowledge (p value = 0.001) and attitude (p value = 0.000) to motivation in the VIA test. It is recommended that women of childbearing age should get a lot of information about early detection and the role of health workers and also families is very important to be able to provide information and support for women of childbearing age to do early detection checks for cervical cancer.Keywords: Knowledge, Attitude, Motivation